2020
DOI: 10.1308/rcsann.2020.0209
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with rivaroxaban after laparoscopic sleeve gastrectomy could reduce the frequency of portomesenteric venous thrombosis

Abstract: Introduction Portal and mesenteric venous thrombosis is a rare but potentially serious complication after laparoscopic sleeve gastrectomy. There are no consistent studies that prove the safety and effectiveness of oral anticoagulant thromboprophylaxis with rivaroxaban after laparoscopic sleeve gastrectomy. The objective was to evaluate the effect of rivaroxaban on the frequency of portal and mesenteric venous thrombosis and its safety profile after laparoscopic sleeve gastrectomy. Materials and methods This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Although associated risk factors such as procedure type and a history of hypercoagulability have been described, specific independent predictors for PVT are not well defined (5,6) . In addition, prior studies have demonstrated that the majority of PVTs occur within the first postoperative month, which supports the use of extended prophylaxis (7,8) . However, appropriate patient selection, effectiveness, and exact duration of any chemoprophylaxis to prevent PVT remains unclear.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although associated risk factors such as procedure type and a history of hypercoagulability have been described, specific independent predictors for PVT are not well defined (5,6) . In addition, prior studies have demonstrated that the majority of PVTs occur within the first postoperative month, which supports the use of extended prophylaxis (7,8) . However, appropriate patient selection, effectiveness, and exact duration of any chemoprophylaxis to prevent PVT remains unclear.…”
Section: Introductionmentioning
confidence: 61%
“…This has therapeutic implications for the duration of extended chemoprophylaxis required to reduce the risk of PVT following bariatric surgery. Extended chemoprophylaxis to prevent PVT has been advocated by some, but patient selection, effectiveness, and duration of therapy has been unclear (7,8) . Based on our findings and the relevant literature we have several recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…PMVT is a rare, life-threatening pathology associated with increased LSG compared with other bariatric procedures. PMVT presentation after LSG is multifactorial and may be associated with genetics, hypercoagulability, acquired thrombophilia, sedentary lifestyle, which lead to blood flow reduction in the lower extremities 28–33. High altitude increased the risk of VTE after LSG for morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…PMVT presentation after LSG is multifactorial and may be associated with genetics, hypercoagulability, acquired thrombophilia, sedentary lifestyle, which lead to blood flow reduction in the lower extremities. [28][29][30][31][32][33] High altitude increased the risk of VTE after LSG for morbidly obese patients. The National Health and Medical Research Council recommends extending LMWH prophylaxis for up to 28 days in high-risk patients who undergo abdominal or pelvic cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 2519 records through database searches, http://clinicaltrials.gov, and reference lists (Figure 1). Twenty‐eight studies were included: 7 cohort studies, 6 case series, and 15 case reports 15–42 . Study characteristics can be found in Table 2.…”
Section: What Is the Efficacy And Safety Of Doacs After Bariatric Sur...mentioning
confidence: 99%